To make the two expressions equivalent, we need to set them equal to each other and solve for G.
-3(x-4) + 2 = -3 + 14 - G
Distributing the -3, we get:
-3x + 12 + 2 = -3 + 14 - G
Combining like terms, we have:
-3x + 14 = 11 - G
To isolate G on one side, we can subtract 11 from both sides:
-3x + 14 - 11 = -G
Simplifying further:
-3x + 3 = -G
Since we want to find the value of G, we can multiply both sides by -1 to get G by itself:
(-1)(-3x + 3) = (-1)(-G)
3x - 3 = G
Hence, the value of G that would make the two expressions equivalent is G = 3x - 3.
What value of G would make the following expressions equivalent -3(x-4)+2and -3+14-g
1 answer